Mimicking bodies and conquering souls. The photographs of the Missionaries of Africa (Kabylia, Aurès, Sahara) - (:unkn) unknown (My University, 2017)
At the end of the 19th century, the Missionaries of Africa chose certain regions of French colonial Algeria to set up their operations and begin the conquest of the souls of a continent that was still little known. How did they see themselves and others in the many photographs they took as soon as they settled in Kabylia, the Aurès and the Sahara? The point of view underlying this visual writing is examined here, drawing on both the images and the missionaries' writings to gain a better understanding of the context in which their exceptional photographs were produced. Presented in eight thematic sections, the photographs lead the reader into the realm of the sensory. What the texts do not say and what the iconography reveals is above all the powerful impact of mutual borrowings that reshaped bodies and clothing. The White Fathers' strategy of merging with the native human environment led them to "change their appearance" as much as the population they wanted to convert. As they expanded their congregation, the Missionaries of Africa spread and eventually globalised the Amazigh costume of men, in particular the burnous, while the populations who had created it abandoned it in favour of manufactured clothing, sewn and fitted according to Western or Eastern fashions.
Keywords: African Research